2006
DOI: 10.1007/s11199-006-9023-1
|View full text |Cite
|
Sign up to set email alerts
|

Gender-related Needs, Challenges, and Dangers in the Immigration Experience in Israel of Emerging Adults from the Former Soviet Union

Abstract: In-depth interviews were conducted to examine gender-related patterns of adaptation and maladaptation, and the relationship between adaptation and relationships (parents, friends, and romantic partners) for 34 emerging adult immigrants from the Former Soviet Union in Israel. Qualitative analysis highlighted gender-related needs, difficulties, and challenges following the immigration experience. Women's adaptation was connected to mutually supportive and empathic relationships with parents, friends, and romanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 54 publications
1
2
0
Order By: Relevance
“…First, parental knowledge was somewhat more strongly associated with better adaptation outcomes (i.e., lower levels of anxiety and better school grades) among girls than boys in all four sub-groups of immigrants, although a statistically significant connection between parental knowledge and school grades was only found among the largest subsample, i.e., among adolescents with an Eastern European background. This result supports previous studies that speak for the gendered effect of parental knowledge on the adaptation of immigrant adolescents (e.g., Walsh and Shulman 2006).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…First, parental knowledge was somewhat more strongly associated with better adaptation outcomes (i.e., lower levels of anxiety and better school grades) among girls than boys in all four sub-groups of immigrants, although a statistically significant connection between parental knowledge and school grades was only found among the largest subsample, i.e., among adolescents with an Eastern European background. This result supports previous studies that speak for the gendered effect of parental knowledge on the adaptation of immigrant adolescents (e.g., Walsh and Shulman 2006).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, studies have shown that the intersectionality of gender and ethnic/ cultural background affects academic achievement (Kim and Calzada 2019) and mental health outcomes (Maleku, 2015;Rask 2018). At the same time, from the perspective of immigrant adolescents' adaptation, girls have been suggested to benefit more from the well-functioning communication with their parents than boys (Walsh and Shulman 2006).…”
mentioning
confidence: 99%
“…The final limitation relates to the inability to explore issues of race and culture in this study. Given the predominantly White sample, it was not possible to explore these complex issues, even though research indicates that ethnicity impacts this experience (e.g., Badger, Nelson, & Barry, 2006;Walsh & Shulman, 2006).…”
Section: Discussionmentioning
confidence: 99%